Developing dendritic cell for SARS-CoV-2 vaccine: Breakthrough in the pandemic - Jonny, Jonny; Putranto, Terawan Agus; Irfon, Raoulian; Sitepu, Enda Cindylosa (Frontiers in Immunology, 2022)
Finding a vaccine that can last a long time and effective against viruses with high mutation rates such as SARS-CoV-2 is still a challenge today. The various vaccines that have been available have decreased in effectiveness and require booster administration. As the professional antigen presenting cell, Dendritic Cells can also activate the immune system, especially T cells. This ability makes dendritic cells have been developed as vaccines for some types of diseases. In SARS-CoV-2 infection, T cells play a vital role in eliminating the virus, and their presence can be detected in the long term. Hence, this condition shows that the formation of T cell immunity is essential to prevent and control the course of the disease. The construction of vaccines oriented to induce strong T cells response can be formed by utilizing dendritic cells. In this article, we discuss and illustrate the role of dendritic cells and T cells in the pathogenesis of SARS-CoV-2 infection and summarizing the crucial role of dendritic cells in the formation of T cell immunity. We arrange the basis concept of developing dendritic cells for SARS-CoV-2 vaccines. A dendritic cell-based vaccine for SARS-CoV-2 has the potential to be an effective vaccine that solves existing problems.